2015
DOI: 10.5539/gjhs.v8n3p43
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Nursery Errors in Healthcare Centers, Isfahan, Iran

Abstract: Background & Aim:Nurse's mistakes usually have a strong effect on the patients trust and satisfaction in the health services systems, and it can also lead to stress and moral contradicts among nurses. This study has aimed to survey the rate of nurses’ mistakes, according to documents in the Isfahan Province during 2007-2012.Methods:The study was a descriptive cross-sectional study. The sample population consisted of all complaints concerning nursing services provided in hospitals, private clinics and other hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
1
0
3
Order By: Relevance
“…Ölçek 5'li likert tipte (1: hiç katılmıyorum, 2: katılmıyorum, 3: kararsızım, 4: katılıyorum, 5: tamamen katılıyorum) olup, 16 maddeden ve 3 alt boyuttan oluşmaktadır. Alt boyutları, tıbbi hata algısı (1 ve 2. maddeler), tıbbi hataya yaklaşım (3,8,10,11,12,13,14. maddeler) ve tıbbi hata nedenleridir (4, 5, 6, 7, 9, 15, 16. maddeler).…”
Section: Hemşirelikte Tıbbi Hataya Eğilim öLçeğiunclassified
See 2 more Smart Citations
“…Ölçek 5'li likert tipte (1: hiç katılmıyorum, 2: katılmıyorum, 3: kararsızım, 4: katılıyorum, 5: tamamen katılıyorum) olup, 16 maddeden ve 3 alt boyuttan oluşmaktadır. Alt boyutları, tıbbi hata algısı (1 ve 2. maddeler), tıbbi hataya yaklaşım (3,8,10,11,12,13,14. maddeler) ve tıbbi hata nedenleridir (4, 5, 6, 7, 9, 15, 16. maddeler).…”
Section: Hemşirelikte Tıbbi Hataya Eğilim öLçeğiunclassified
“…Çok merkezli bir çalışmada, mesleki yaşamı boyunca her 5 hemşireden 2'sinin tıbbı hata yaptığı, en sık yapılan tıbbi hataların hastanın tedavisini geciktirme veya uygulamama (%22.7), cihazı kontrol etmeden hastada kullanma (%19.6) olduğu ve bu hataların %4'ünün hastaya zarar verdiği belirlenmiştir (9). Hasta zarar görmese bile hemşireler tarafından yapılan hatalar, hastanın sağlık hizmetine olan güvenini ve memnuniyetini ciddi şekilde etkilemektedir (9)(10)(11). Yapılan çalışmalar, hemşirelere yönelik tıbbi hata şikâyetlerinin (%9.8) (10), yetersiz iletişim, kayıtların eksik tutulması, hasta savunuculuk rolünü yerine getirmeme, verilen bakımın standartların altında kalması, değerlendirme ve izlemin eksik yapılması ile ilgili olduğunu (6) ve yasal süreçte ortaya çıkan en önemli nedenin ihmal olduğunu (10) ortaya koymuştur.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The national rate of clinical negligence in Iranian healthcare settings is not known. A cross‐sectional study on all types of complaints registered against nurses in an urban area of Iran from 2007 to 2012 showed that negligence (65%) was one of the main causes of court rulings (Ayoubian et al., 2015). Another Iranian study reported that 36% of patients’ complaints were related to negligence (Hayatbakhsh Abbasi et al., 2020).…”
Section: Introductionmentioning
confidence: 99%